Research on climate change in social psychology publications: A systematic review. Issue 2 (9th April 2021) - Tam, Kim‐Pong; Leung, Angela K.‐y.; Clayton, Susan
Abstract : There is a strong scientific consensus that anthropogenic climate change is happening and that its impacts can put both ecological and human systems in jeopardy. Social psychology, the scientific study of human behaviours in their social and cultural settings, is an important tool for understanding how humans interpret and respond to climate change. In this article, we offered a systematic review of the social psychological literature of climate change. We sampled 130 studies on climate change or global warming from 80 articles published in journals indexed under the "Psychology, social" category of Journal Citation Reports . Based on this sample, we observe that social psychologists have produced an impressive canon of research on this pressing topic, the strengths of which include diversity of research designs, outcome variables, and theoretical angles. However, there are some gaps in this literature, including weak presence of authors and data from non‐Western, developing, and nondemocratic societies, lack of cross‐cultural comparisons, reliance on young and Amazon MTurk samples, lack of attention to some crucial outcome variables, and overemphasis on intrapersonal and intrapsychic processes. We recommend that future social psychological research on climate change needs to broaden geographical and demographic representation, examine study outcomes other than mitigation behaviour, and adopt more "social" theoretical perspectives. We also offer suggestions as to how these needs can be addressed.